5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)
It can be simplified to: 3a^2 +10a+7 or factored as (3a+7)(a+1)
If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
= a + b - 2
a = 3a + 4 0 = 2a + 4 2a = -4 a = -2
3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2
It is then 2 when all terms are added together
2a^3 + 54 can first be factored into 2 (a^3 + 27). This can then be factored out to 2 (a + 3) (a^2 - 3a + 9).
Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).
7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a
a + b - 2 is the answer in simplest terms. without telling us what a or b is this is the most accurate answer.
a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.
It is 6a + 4
The GCF of 2a amd 3a is 1a. This is because 2 and 3 doesn't have a common factor so it has to be 1 and the variables a and a are the same so the answer is 1a
Simplifying a = 3a + 12 Reorder the terms: a = 12 + 3a Solving a = 12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. a + -3a = 12 + 3a + -3a Combine like terms: a + -3a = -2a -2a = 12 + 3a + -3a Combine like terms: 3a + -3a = 0 -2a = 12 + 0 -2a = 12 Divide each side by '-2'. a = -6 Simplifying a = -6
= 3 X 2 = 6 = a X a = a2 (a square) = 6a2 + 5 Answer
6a2 - 8ab + 2aas you can see a is common to all terms. And 2 is a factor of 6,8, and 2. So 2a is a factor of all three terms:2a(3a-4b+1)
2(a+b) is 2a plus 2b in factored form.
2a2 x 3a-3 = (2 x 3)a(2 + -3) = 6a-1
I guess you mean: 2a^2+6a Well in this case you take 2a out of the bracket and then you're left with a+3 inside. 2a(a+3a)